VALIDITY AND RELIABILITY OF A METHODOLOGICAL INSTRUMENT FOR MEASURING VERBAL-VISUAL COGNITIVE STYLES IN ADVERTISING - L. Spasova (Trakia Journal of Sciences)
This study has the following objective: to validate, adapt and modify a scale from Kirby, Moore and Schofield – VVQ, based on Richardson’s scale, to be applied in measurements of advertising influence. The statistical methods applied in the study were factor analysis using principal component analysis (PCA) and Varimax orthogonal rotation with Kaiser normalization, as well as correlation analyses to establish the linear relationship between the VVQ subscales (N=425). The results of a factor analysis (PCA) indicated that a 3-factor solution was acceptable for the present data, forming 3 subscales in the following order: for dreamers, for visualizers, and for verbalizers. Visualization was found to be more pronounced than verbalization in the individuals studied, and the vividness of sleep was more important in building individuals' verbal abilities than visual abilities. The results may be useful for researchers of cognitive styles of individuals as well as their segmentation in marketing, advertising and media.